HIV, alcohol dependence, and the criminal justice system: a review and call for evidence-based treatment for released prisoners. - Springer, Sandra A; Azar, Marwan M; Altice, Frederick L (The American journal of drug and alcohol abuse, 2011)
People with both HIV and alcohol use disorders (AUDs) are disproportionately concentrated within the U.S. criminal justice system; approximately one-quarter of all people with HIV cycle through the system each year. HIV-infected prisoners with AUDs face many obstacles as they transition back to the community. Specifically, although they have impressive HIV treatment outcomes during the period of incarceration while they are free from alcohol; upon [corrected] release, however, they face inordinate challenges including relapse to alcohol use resulting in significant morbidity and mortality.
Keywords: Alcoholism; Criminal Law; Evidence-Based Medicine; HIV Infections; Humans; Prisoners; United States